Effects of Concentration of Triethanolamine and Annealing Temperature on Band Gap of Thin Film of Tin Sulphide Prepared by Chemical Bath Deposition Method - Joshi, Leela Pradban; Risal, Laxmi; Shrestha, Shankar Prasad (Journal of Nepal Physical Society, 2016)
Thin films of Tin Sulphide (SnS) were deposited by chemical bath deposition technique using a precursor solution of stannous chloride (SnCl2.2H2O), thioacetamide (TA), triethanolamine (TEA), ammonia (NH3), and distilled water. The effects of concentration of triethanolamine and annealing temperature on the growth of SnS films were studied to optimize the growth conditions. X-ray diffraction study shows the deposited films were polycrystalline in nature and orthorhombic in structure. The optical direct and indirect band gap values of SnS films prepared with 15ml of TEA were found to be 1.76 eV and 0.89 eV respectively. Annealing the sample prepared with 12ml of TEA results increase in band gap from 1.79eV to 3.32eV. Journal of Nepal Physical Society, 2015, Vol. 3(1): 1-5